KEMAMPUAN LITERASI MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR DI MTS DARUL HIKMAH KEDUNG JEPAR - Nailil Muna Auliya; Amin Suyitno; Mohammad Asikin (FMIPA UNIVERSITAS NEGERI MALANG, 2021)
This study aims to describe students' mathematical literacy skills in terms of learning independence. This research is a descriptive qualitative research. The place of research is at MTs Darul Hikmah Kedung Jepara. The research subjects were seventh grade students of MTs Darul Hikmah who were selected through purposive sampling technique. The data was collected by giving a test of mathematical literacy skills and semi-structured interviews. The results showed that students with high learning independence category were able to solve well problems of low and medium level mathematical literacy skills. Students with moderate learning independence category were able to solve low and medium level mathematical literacy skills, but there were still errors. Students with low learning independence category are only able to solve low level questions well.